Segurança na cirurgia da tiróide: neuromonitorização e selagem vascular - Luis Miguel Torres Morientes; Eduardo Tamayo Gómez; Liliana Filipa Invencio da Costa; Marta Alonso Mesonero; María San Millán González; Jaime Santos Pérez (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Introduction: Thyroid surgery carries significant risks and complications such as recurrent laryngeal nerve paralysis and postoperative suffocating hematoma. The most recent advancement providing safety is intraoperative neuromonitoring (IONM) of the recurrent laryngeal nerve (RLN) and the advances in hemostasis systems.